Spectroelectrochemical Experiment for Studying Water Oxidation with a Nickel Oxide Catalyst - González Flores, Diego (2020)
Electrochemical and spectroelectrochemical techniques are very important for characterizing energy materials. In the search for new sources of renewable energy, water splitting for hydrogen production and CO2 reduction is attracting significant attention. These applications require efficient and durable catalysts and a detailed understanding of the underlying catalytic mechanism. Here, we experimentally study electrodeposited nickel oxide as a catalyst for electrochemical water oxidation by combining UV–vis and electrochemical techniques, with emphasis on revealing the interplay between catalytic activity and physical changes in the catalyst. Specifically, the spectroelectrochemical characterization of the catalyst at different pH enables students to establish correlations between catalytic activity, pH, and physical changes in the catalyst. Students are also introduced to fundamental principles of electrocatalysis such as Tafel plots, TOF (turnover frequency), and midpoint potential. Moreover, they are guided toward the reliable interpretation of optical absorption and electrochemical data, along with the conceptual aspects behind these techniques.